2002
DOI: 10.1016/s0002-9440(10)64172-7
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Target Gene, SKP2, within the 5p13 Amplicon That Is Frequently Detected in Small Cell Lung Cancers

Abstract: We investigated DNA copy-number aberrations in 22 cell lines derived from small cell lung cancers (SCLCs) using comparative genomic hybridization. A minimal common region at 5p13, within the 5p11-p13 amplicon that was most frequently involved, harbored the CDH6, PC4, and SKP2 genes. These three genes showed amplification and consequent overexpression in the SCLC cell lines. SKP2 positively regulates progression of cell cycle by targeting several regulators, such as the cell-cycle inhibitor p27(KIP1), for ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 44 publications
7
133
0
1
Order By: Relevance
“…3). In particular, Skp2 levels have been examined in human tumors and have been shown to correlate with grade of malignancy [51,[53][54][55][56][57]69,70]. Similar findings have been reported for high levels of cyclin E and A (reviewed in [58]).…”
Section: P27 and Human Cancersmentioning
confidence: 69%
“…3). In particular, Skp2 levels have been examined in human tumors and have been shown to correlate with grade of malignancy [51,[53][54][55][56][57]69,70]. Similar findings have been reported for high levels of cyclin E and A (reviewed in [58]).…”
Section: P27 and Human Cancersmentioning
confidence: 69%
“…Overexpression or Regulation of RASSF1A by Skp2 at G 1 -S transition MS Song et al amplification of Skp2 has been reported in a large number of human cancers (Yokoi et al, 2002) and transgenic expression of Skp2 in mice leads to tumor formation, suggesting that Skp2 is oncogenic (Gstaiger et al, 2001;Latres et al, 2001). Skp2 targets p27, cyclin E and FOXO1 for degradation in a phosphorylationdependent manner (Marti et al, 1999;Nakayama et al, 2000;Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role as a putative tumor suppressor in normal cellular growth, some other studies also suggest that PC4 may also be involved in the tumorigenesis, probably through the activation or synergizing of other genes required in the pathogenesis of cancer. [20][21][22][23][24] A possible involvement of PC4 in oncogenesis in a chemically induced rat pancreatic B-cell tumor was first observed in 1984. 21 Using a general cDNA screen method, Soma et al were able to identify a clone encoding for 119 amino-acid residues that showed a clearly positive reaction only with a probe derived from rat pancreatic B-cell tumor, but not the probe derived from normal islet B cells.…”
Section: Downregulation Of Pc4 Inhibits Tumorigenicity Of A549 Cells mentioning
confidence: 99%
“…Comparative genomic hybridization studies indicated that PC4 was one of the three genes that showed amplification and consequent over expression in the NSCLC cell lines. 22 Gene expression profiling indentified that the expression of PC4 in invasive intraductal papillary mucinous neoplasm of the pancreas was increased 28-fold compared with normal pancreatic epithelium. 23 Statistical analysis of gene expression data from primary colorectal carcinomas, liver metastases and carcinomatoses identified PC4 as one of the top 20 genes upregulated in carcinomatoses.…”
Section: Downregulation Of Pc4 Inhibits Tumorigenicity Of A549 Cells mentioning
confidence: 99%
See 1 more Smart Citation